PENERAPAN INTEGRASI PREFERENCE SELECTION INDEX DENGAN FAILURE MODES AND EFFECTS ANALYSIS PADA EVALUASI PRIORITAS POTENSI RESIKO KERUSAKAN POMPA SENTRIFUGAL - Savior Pongai; Agung Sutrisno; Irvan R. Rondonuwu (Jurnal Tekno Mesin, 2023)
Production machinery is one of the production factors that has an important role so that machine maintenance is very important to be studied. Related to this, this study aims to determine the priority of engine damage risk in centrifugal pumps. In its study, this study uses an integration between the Failure Modes and Effects Analysis (FMEA) method with the Preference Selection Index (PSI) method. From the results of the application of the integration of the Failure Modes and Effects Analysis (FMEA) method with the Preference Selection Index (PSI) method in the priority evaluation of the potential risk of damage to centrifugal pumps shows 6 types of damage that commonly occur in the two pumps, namely scorched electro motor rewinding, worn bearing casing, worn pump shaft, corrosion impeller, worn bearings, worn shaft housing. Then for the priority ranking results, the risk of damage to the first centrifugal pump falls on corrosion on the impeller which is the highest priority type of damage with a preference score of 0.86. And for centrifugal pumps, the two types of damage with the highest preference score are scorched motor eletro rewinding due to overheating with a preference score of 0.74 Then for treatment proposals for handling activities, periodic checks, periodic handling, and periodic changes are generally carried out,  Keywords: Preference Selection Index (PSI) method, Failure Modes and Effects Analysis (FMEA), centrifugal pump   ABSTRAK Mesin produksi merupakan salah satu faktor produksi yang memiliki peran penting sehingga perawatan mesin sangat penting untuk dikaji. Terkait dengan hal tersebut, penelitian ini bertujuan untuk menentukan prioritas resiko kerusakan mesin pada pompa sentrifugal. Dalam pengkajian nya penelitian ini menggunakan integrasi antara metode Failure Modes and Effects Analysis (FMEA) dengan metode Preference Selection Index (PSI). Dari hasil penerapan integrasi metode Failure Modes and Effects Analysis (FMEA) dengan metode Preference Selection Index (PSI) pada evaluasi prioritas potensi resiko kerusakan pompa sentrifugal menunjukan 6 jenis kerusakan yang umum terjadi pada kedua pompa yang ada yaitu rewinding elektro motor hangus, casing bearing aus, shaft pompa aus, impeller korosi, bearing aus, housing shaft aus. Kemudian untuk hasil perangkingan prioritas resiko kerusakan pompa sentrifugal pertama jatuh pada korosi pada impeller yang merupakan jenis kerusakan dengan prioritas tertinggi dengan skor preferensi 0,86. Dan untuk pompa sentrifugal kedua jenis kerusakan dengan skor preferensi tertinggi adalah rewinding eletro motor hangus akibat overheat dengan skor preferensi 0,74. Kemudian untuk usulan perawatan pada umumnya dilakukan pengecekan, penanganan, dan pergantian komponen berkala. Kata kunci: Metode Preference Selection Index (PSI), Metode Failure Modes and Effects Analysis (FMEA), pompa sentrifugal.